Effect of household couple counselling for male involvement on the utilization of postnatal services at 1 week in Ibanda district, Uganda; A cluster randomized community trial - Bagenda, Fred Norman; Batwala, Vincent; Orach, Christopher Garimoi; Kabakyenga, Jerome; Nabiwemba, Elizabeth; Atuyambe, Lynn (International Journal of Scientific Research Updates, 2023)
Introduction: Prompt and Skilled postnatal care attendance coupled with skilled Antenatal and delivery care can drastically reduce maternal morbidity and mortality and also improve newborn outcomes. Research shows that men are decision makers in the home but they may also restrict resources, hence preventing women and children from health care seeking. But however if involved men may lead to better health care seeking behavior and better utilization of Antenatal care, delivery and postnatal care services. The postnatal care attendance at 1 week is low in Uganda, Ibanda district reported 4% in 2018. The aim of this study was to innovate, implement and document an intervention of house hold couple counseling for male involvement and compare the intervention and control clusters on the utilization of postnatal care services at 1 week. Methods: This was a two arm cluster randomized Community trial with a parallel design with the aim of comparing utilization of postnatal care services. It was carried out in two intervention parishes and two control parishes and was a superiority trial to test if the intervention of household couple counseling would improve utilization of postnatal care services. Results: The intervention arm had 200 respondents while the control had 213. The mean age was 27.3years (SD 6.8). Ninety-one point five percent of mother had used skilled delivery services in the intervention compared to 78.4% in the control. Seventy-Five percent attended postnatal care at 1week in the intervention as compared to 21.1% in the control (OR 11.2, P<0.001). The activity that are statistically significantly associated with utilization of postnatal services utilization is providing transport to the postnatal clinic (AOR 30.8, P<0.001) comparing the intervention and control clusters. The others included; accompanying to antenatal clinic, partner attending antenatal clinic, providing transport for delivery, escorting partner for delivery, providing psychological support during delivery and providing necessary drugs during delivery and PNC period but these were not statistically significant. Conclusion: The study demonstrated that the intervention of household couple counseling for increased male partner involvement improved significantly utilization of postnatal care services. Interventions to improve utilization of postnatal care services should focus on involving male partners to do the supportive activities which help their pa
Keywords: Postnatal service utilization; Male involvement; Supportive activities; Antenatal care